Biological evaluation of the substitution of dicalcium phosphate for "Trinidad de Guedes" phosphorite in broilers - Valera, M.; Gutiérrez, Odilia; Rodríguez, Bárbara (Cuban Journal of Agricultural Science, 2018)
In order to use phosphorite, from new ores of "Trinidad de Guedes" deposit, as a supplement of Ca and P for broilers, the dicalcium phosphate of the diet was replaced by 50 and 100 % of phosphorite. A biological evaluation was carried out and the effectof this substitution on liveweight, relative weight of carcasses and of some organs and blood indicators, was analyzed. An amount of 57 animals was used, which were taken from an experiment of productive performance with 300 broilers of HE21 hybrid from 1d old, distributed according to a completely randomized design. Liveweight was determined at 35 and 42 d, and after slaughter, relative weight of carcasses, liver, spleen, kidney and pancreas was also determined, as well as hemoglobin and hematocrit. For liveweight, there were no differences between control and treatments with the substitution of dicalcium phosphate in both studied periods (1.53 vs. 1.53 and 1.49 kg; 1.71 vs. 1.66 and 1.71 kg). Regarding relative weight of carcasses and organs, and to hematological indicators, there were no differences between control and treatments, for either period. Results suggest the use of Trinidad de Guedes phosphorite to replace dicalcium phosphate as a Ca and P supplement for broilers, without affecting liveweight, relative weight of carcasses and organs, as well as hemoglobin and hematocrit.Key words: supplement, liveweight, carcass, organs